Assessing the behaviour of wireworms in soil using non-destructive imaging techniques - Booth, Samuel, W. (2023)
Wireworms are the larval stage of click beetles, and some species are significant agricultural pests, causing stand reduction in cereal crops through consumption of freshly planted seeds and seedlings. Their management is difficult due to the long-lived nature of the larvae in soil, an ability to recover after intoxication, and restrictions on the use of previously effective compounds. Whilst much previous work exists on treatment efficacy in terms of ability to cause mortality, the sub-lethal effect on behaviour of these compounds has not been comprehensively studied. Understanding these sub-lethal effects alongside a treatments lethal effect to reduce population levels is vital in developing treatments that can effectively reduce yield losses. Studies of this kind are difficult due to the opaque nature of soil. X-ray Computed Tomography (CT) is a technique widely used across rhizosphere research as it is able to non-destructively image soil characteristics and root interactions in the soil.